2022
DOI: 10.3390/ijerph192013379
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Lifestyle Changes, Risk Perception and Anxiety during COVID-19 Lockdowns: A Case Study in Xi’an

Abstract: The outbreak of COVID-19 dramatically changed individuals’ lifestyles, which in turn triggered psychological stress and anxiety. Many previous studies have discussed the relationships between lifestyle changes and anxiety and risk perception and anxiety independently. However, few papers have discussed these factors in a comprehensive and systematic manner. We established a six-dimensional system to assess changes in individuals’ lifestyles, which include dietary habits, physical activity (PA), sleep, screen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that smoking cessation was related to the improvement of depression and anxiety, while smoking and drinking had a negative impact on anxiety and depression. [44][45][46][47][48] Physical activity reduction was a risk factor for anxiety and depression of residents, which was consistent with previous researches. [49][50][51] In addition, this work also found that BMI was not significantly related to anxiety and depression, which was inconsistent with the research results of Flanagan EW and Klaser K, who found that BMI was significantly related to anxiety and depression during the epidemic, [52,53] but consistent with the research results of Alves JM and Auny FM.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that smoking cessation was related to the improvement of depression and anxiety, while smoking and drinking had a negative impact on anxiety and depression. [44][45][46][47][48] Physical activity reduction was a risk factor for anxiety and depression of residents, which was consistent with previous researches. [49][50][51] In addition, this work also found that BMI was not significantly related to anxiety and depression, which was inconsistent with the research results of Flanagan EW and Klaser K, who found that BMI was significantly related to anxiety and depression during the epidemic, [52,53] but consistent with the research results of Alves JM and Auny FM.…”
Section: Discussionsupporting
confidence: 91%
“…This was different from a study conducted during the Italian lockdown [32]. This could be related to the fact that residents' behavior and lifestyle had been changed at the end of the second year of the COVID-19 pandemic [3,4]. Therefore, in future research, it is necessary to consider not only residents' behaviors and habits but also their landscape preferences, which will be conducive to the formation of more targeted strategies.…”
Section: The Anxiety Remission Effects On Residents With Different La...mentioning
confidence: 79%
“…During the COVID-19 pandemic, many countries applied lockdown rules in an attempt to flatten their epidemic curves [1,2]. Because of the numerous and unpredictable risks of the pandemic and of these rules confining people to their homes, people have faced social isolation, changes in lifestyle, and psychological problems [3,4]. Evidence has shown that staying at home throughout the pandemic or shielding at all were strongly associated with greater risk of elevated depressive symptoms, anxiety, poorer quality of life and lower life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the study found that the COVID-19 epidemic negatively impacted the psychological well-being of undergraduate medical students, with increased incidence as well as levels of anxiety and stress ( 32 35 ). Fourth, in terms of methods of stress relief during COVID-19, scholars have explored ways to relieve stress, such as improving lifestyle and adopting positive health behaviors ( 36 40 ). Mattioli et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the study found that the COVID-19 epidemic negatively impacted the psychological well-being of undergraduate medical students, with increased incidence as well as levels of anxiety and stress (32)(33)(34)(35). Fourth, in terms of methods of stress relief during COVID-19, scholars have explored ways to relieve stress, such as improving lifestyle and adopting positive health behaviors (36)(37)(38)(39)(40). Mattioli et al demonstrated that isolation is associated with stress and depression, and that global action must be engendered to support healthy diet and physical activity, thereby promoting good lifestyles (41).…”
Section: Introductionmentioning
confidence: 99%